Revision of the sesarmid crab genera Labuanium Serène and Soh, 1970, Scandarma Schubart, Liu and Cuesta, 2003 and Namlacium Serène and Soh, 1970 (Crustacea: Decapoda: Brachyura: Sesarmidae), with descriptions of four new genera and two new species. Issue 7 (16th February 2020) - Naruse, Tohru; Ng, Peter K.L.
ABSTRACT: The systematics of the arboreal sesarmid crab genera Labuanium Serène and Soh, 1970 and Scandarma Schubart, Liu and Cuesta, 2003 is revised. Also included is the poorly known genus Namlacium Serène and Soh, 1970, which is morphologically similar to Labuanium and may also be arboreal in habit. The present study restricts Labuanium to its type species, L. politum (De Man, 1887), and congeners are transferred to Scandarma, Geosesarma De Man, 1892, and three new genera established herein: Circulium gen. nov., Shinobium gen. nov. and Mindanium gen. nov. Two new species of Scandarma are described from Papua New Guinea and Madagascar. Sesarma jacquinoti Ortmann, 1894, previously regarded as a synonym of Scandarma gracilipes (H. Milne Edwards, 1853) (comb. nov.), is here shown to be a junior synonym of Sesarmops angustifrons (A. Milne-Edwards, 1869). Labuanium schuetteii (Hess, 1865) is regarded as conspecific with Scandarma gracilipes (H. Milne Edwards, 1853) (comb. nov.) and the lectotype of the latter species (here designated) is also selected as the neotype of the former, making the two names objective synonyms. Material which had been identified as ' Labuanium finni Alcock, 1900' by Pretzmann (1984) from the South Andaman Islands is actually the poorly known Geosesarma thelxinoe (De Man, 1908), which is here referred to a new genus, Andamanium gen. nov. Sesarma finni Alcock, 1900 s.s. is herein assigned to Scandarma. Namlacium crepidatum (Calman, 1925), the only species in the genus, is redescribed and figured and compared with Labuanium and Scandarma . Keys to species of Circulium and Scandarma are provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:414B8DAA-584F-4070-A355-83B583D0D017